Pattern and frequency of uterine pathologies among hysterectomy specimens in rural part of northern India: a retrospective secondary data analysis - Chaturvedi, Vineet; Dayal, Seema; Srivastava, Dhiraj; Gupta, Vivek; Chandra, Anuj (Indian Journal of Community Health, 2014)
Background: Hysterectomy is the most commonly performed gynecological surgery throughout the world. Over the last several years reported cases of hysterectomy was increasing in numbers. However, similar studies from Etawah district with high prevalence of hysterectomy are lacking. Therefore, we have conducted this study to identify the pattern of pathologies identified in hysterectomy specimen and to correlate the pathological findings with the age group of the patient along with frequency of benign, malignant pathologies identified. Material and method: This study was conducted on 870 hysterectomy specimen who reported to pathology department .They were compared in terms of age of the patients and pathology of hysterectomy specimens. Result: Out of the hysterectomy specimens, pathological findings were seen in 850 hysterectomies. Most common lesion was leiomyoma (22.47%) followed by Adenomyosis (21.76%) ,Endometrial hyperplasia (14.00 %), ovarian cyst (9.29%), Endometrial atrophy (8.70%), Endometritis (7.76 %), Endo cervical polyp (5.64), Carcinoma intra epithelial neoplasm (3.52%), Endometrial polyp (3.17%), Carcinoma cervix (1.17%), Carcinoma ovary (1.05%), Benign ovarian tumor (0.58%),Carcinoma endometrium(0.35%), Myometritis (0.35%), Chorio carcinoma (0.11%) The most common age group was (40-49) years. Conclusion: Our data suggest that leiomyoma was the most common pathology seen in hysterectomy .The common age group for hysterectomy was (40 -49) years. Benign pathologies are more frequent in hysterectomy than malignant. Histopathology is mandatory for ensuring diagnosis and thus management, in particular of malignant disease.